A Phase 1b Trial to Assess the Pharmacokinetics of Ezutromid in Pediatric Duchenne Muscular Dystrophy Patients on a Balanced Diet. Issue 7 (16th January 2019) - Muntoni, Francesco; Tejura, Bina; Spinty, Stefan; Roper, Helen; Hughes, Imelda; Layton, Gary; Davies, Kay E.; Harriman, Shawn; Tinsley, Jonathon
Abstract: Ezutromid (SMT C1100) is a small‐molecule utrophin modulator that was developed to treat Duchenne muscular dystrophy (DMD). Previous clinical trials of this agent revealed lower exposure in DMD patients compared with healthy volunteers, which may reflect differences in diet. This study evaluated the pharmacokinetics of ezutromid in patients with DMD who followed a balanced diet. This was a multicenter, double‐blind, placebo‐controlled, ascending single and multiple oral dose study. Twelve pediatric patients were randomly allocated to 1 of 3 treatment sequences within which were 3 treatment periods of 2 weeks each. Each patient received, in a dose‐escalating fashion, 1250 mg and 2500 mg twice daily (BID) of ezutromid administered orally as a microfluidized suspension (F3) with placebo in the other treatment period. Throughout the study, patients followed a balanced diet including recommended proportions of major food groups and administration of drug accompanied with 100 mL of full‐fat milk. This approach improved the absorption of ezutromid, resulting in higher systemic exposure, with considerable variability in exposure between patients at each dose level. Single and multiple oral doses of 1250 mg and 2500 mg BID were considered safe and well tolerated. No severe or serious adverse events and no study discontinuations due to adverse events were reported. This study provides assurance that, with the formulation tested (F3) and instructions regarding food (balanced diet and whole‐fat milk), 2500 mg BID of ezutromid achieves plasma concentrations that, based on preclinical studies, should be able to modulate utrophin expression in future clinical trials.